Menavigasi Transisi Hijau: Analisis Kualitatif Tantangan dan Dinamika Pemangku Kepentingan dalam Implementasi Green Port di Indonesia - Ariadi, Tiara Sekarwati; Hagassi, Rizki; Santy, Ni Nyoman Parahita; Raharjo, Setyo Slamet; Baharudin, Irwan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
As global pressure for decarbonizing the maritime sector intensifies, ports worldwide, including in Indonesia, are facing demands to transform into green ports. This study aims to conduct an in-depth analysis of the multidimensional challenges and complex stakeholder dynamics in the implementation of the green port concept in Indonesia. Using a descriptive qualitative method based on a documentary study, this research integrates Stakeholder Theory and Institutional Theory to dissect the interactions among actors and the external pressures shaping sustainability strategies. The main findings indicate that the green transition in Indonesian ports is hindered by three primary challenges: (1) economic constraints related to high investment and operational costs, (2) socio-economic trade-offs that risk impeding regional economic growth, and (3) fragmented governance among government institutions. Stakeholder analysis identifies fundamental conflicts of interest among the government, port operators, the private sector, and local communities. The implication of this research is the need for a shift from showcase projects to a holistic, systemic transformation, supported by a robust multi-stakeholder governance platform and effective incentive schemes to encourage widespread adoption of green technology.